2013
DOI: 10.1371/journal.pone.0059603
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Curcumin in Human Retinal Pigment Epithelial Cells

Abstract: BackroundCurcumin from turmeric is an ingredient in curry powders. Due to its antiinflammatory, antioxidant and anticarcinogenic effects, curcumin is a promising drug for the treatment of cancer and retinal diseases. We investigated whether curcumin alters the viability and physiological properties of human retinal pigment epithelial (RPE) cells in vitro.Methodology/Principal FindingsCellular proliferation was investigated with a bromodeoxy-uridine immunoassay, and chemotaxis was investigated with a Boyden cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 60 publications
4
28
0
1
Order By: Relevance
“…Our study demonstrates significant cytotoxic effects of standard curcumin in RPE cells at concentrations >20 μM. These findings are in agreement with the data of previous studies in which curcumin exhibited pro-apoptotic effects in RPE cells at concentrations of approximately 20 μM [10,11]. These concentrations are in the same concentration range that is supposed to be effective in cancer cells [48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study demonstrates significant cytotoxic effects of standard curcumin in RPE cells at concentrations >20 μM. These findings are in agreement with the data of previous studies in which curcumin exhibited pro-apoptotic effects in RPE cells at concentrations of approximately 20 μM [10,11]. These concentrations are in the same concentration range that is supposed to be effective in cancer cells [48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 93%
“…However, recent reports of curcumin-mediated retinal cytotoxicity [10][11][12][13] could imply that chronic intake of curcumin negatively affects retinal function. The aims of this study are the following: (1) to assess and characterize the cytotoxic and oxidative effects of nano-curcumin and standard curcumin in RPE cells in vitro, and (2) to investigate the in vitro effects of nano-curcumin and standard curcumin on proteasome expression and activity in RPE cells, to ascertain whether they can be used as proteasome-modulating agents in retinal disorders.…”
mentioning
confidence: 99%
“…In a study for investigation of cytotoxic effects of curcumin on normal cells (spleen lymphocytes and NIH3T3) and cancer cells (EL4 and MCF7), curcumin at concentrations of 5 to 80 nmol/ml demonstrated that the uptake of curcumin in cancer cells was higher than normal cells so cytotoxic effects of curcumin on cancer cells is more than normal cells (Kunwar et al, ). Research projects on human epithelial pigment cells revealed that concentrations higher than 10 μM of curcumin reduced proliferation of cells, and also, 1 to 50 μM of curcumin decreased the number of living and viable cells (Hollborn et al, ). On vascular smooth muscle cells (VSMCs) and endothelial cells that isolated from aorta, curcumin showed toxic effects on normal cells and inhibited cell proliferation at the concentration of 5 μM.…”
Section: Resultsmentioning
confidence: 99%
“…After administration of curcumin, the expression of these antioxidant genes was significantly up-regulated (Figure 6A). Recent evidences have demonstrated that curcumin may modulate growth factor expression and can act as a therapeutic agent (Epstein et al, 2010; Hollborn et al, 2013). PDGF, VEGF, and IGFBP-2 have been shown to be involved in regular RPE functions or retinal diseases (Epstein et al, 2010; Hollborn et al, 2013).…”
Section: Resultsmentioning
confidence: 99%